2018
DOI: 10.1016/j.jclepro.2017.10.267
|View full text |Cite
|
Sign up to set email alerts
|

Pricing the permission of pollution: Optimal control-based simulation of payments for the initial emission allowance in China

Abstract: China has modified its pollution control policy system with such price tools as the pollution charge (PC) policy and the payment for initial emission allowance (PIEA) policy. The aim of PC policy is to compensate for the environment damage caused by pollutants, while PIEA is in charge of the initial emission allowance (IEA) within the emission trading system (ETS). However, since the implementation of PIEA, it has been criticized as redundant because of the similar pricing scheme with the PC. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Another related research area is decision-making by manufacturers under the emissions trading system. During the past decade, scholars have conducted several exploratory studies regarding decision-making processes within emission-dependent manufacturers under the emissions trading system, including production decision and optimisation (Li, 2013;Manikas & Godfrey, 2010;Song et al, 2017;Zhang et al, 2011), emission permits trading strategy (Gong & Zhou, 2013;Haita, 2014) and investment strategy in pollution control (Guo et al, 2018;Lundgren, 2003;Wang et al, 2018). Svensson and Berntsson (2011) discussed the external factors that affect production and investment planning among manufacturers; they concluded that changes in trading price have a significant impact on investment planning by manufacturers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another related research area is decision-making by manufacturers under the emissions trading system. During the past decade, scholars have conducted several exploratory studies regarding decision-making processes within emission-dependent manufacturers under the emissions trading system, including production decision and optimisation (Li, 2013;Manikas & Godfrey, 2010;Song et al, 2017;Zhang et al, 2011), emission permits trading strategy (Gong & Zhou, 2013;Haita, 2014) and investment strategy in pollution control (Guo et al, 2018;Lundgren, 2003;Wang et al, 2018). Svensson and Berntsson (2011) discussed the external factors that affect production and investment planning among manufacturers; they concluded that changes in trading price have a significant impact on investment planning by manufacturers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…色技术深化 [1] 、 成果转化 [2] 、 评估审查等绿色服务产 业发展提出更高的要求 [3] 评估、 排放权交易等单个政策工具的经济、 环境效 益评估上。①在绿色服务产业政策的经济效益方 面: Guerra 等 [5] 研究强制性环境影响评估对海洋项 目的影响, 发现所有项目都受益于环境影响评估; 于扬等 [6] 研究绿证交易和发电配额制度的财税减负 效应, 发现绿证交易可以降低企业配额履约成本和 电价政策的财税负担; 任胜钢等 [7] 以排污权交易制 度为对象检验 "波特假说" , 发现排污权交易制度可 以通过资源配置和技术创新两条路径提高全要素 生产率; 韩超等 [8] 发现清洁生产标准规制对生产率 的影响前期为负, 后期当标准规制带来的学习效应 超过挤出效应, 对生产率的影响是正向的; 任晓松 等 [9] 将碳交易市场和交易权相关政策作为外生冲击 构造准自然实验, 研究其在不同规模企业间的经济 效益及实现路径, 也验证了绿色服务产业政策的经 济效益; ②在绿色服务产业政策的环境效益方面: Xian 等 [10] 发现碳排放交易体系可以降低减排的机会 成本和边际成本, 当交易体系全面运行时几乎所有 地区都存在碳排放边际成本的节省; Shen 等 [11] 运用 DID 方法验证了碳排放权交易制度的减排效果, 发 现采用事后配额分配制度效果更好; Zhang 等 [12] 则 发现碳权交易制度的减排潜力及其对减排的贡献 会随时间推移不断增加。除了碳排放, 绿色服务产 业政策环境效益的另一个热点集中在污染物排放 上, 如 Guo 等 [13] 通过仿真发现排污费 (PC) 政策补偿 了排放损害, 初始排放配额支付 (PIEA) 政策增加了 企业排放成本, 进而降低中国大部分地区的 COD 排 放。③绿色服务产业政策同时作用于经济和环境 效益: 刘海英等 [14] 研究了能权政策和碳排放权交易 政策组合对产出、 节能、 减排的影响, 发现政策组合 使用比单独使用具有更好的效益, 且产出、 节能和 减排能共同提高绿色全要素生产率; Yang 等 [15] 也发 现碳排放交易政策具有促进就业和减排的双重效 应; Chen 等 [16] 高污染、 高能耗产业向低污染、 低能耗产业转移, 实 现产业结构的绿色转型 [18] , 一些强制管控型的政策 工具可能在短期内增加产业的环境成本, 但长期看 将倒逼创新投入, 调整资源配置 [19] [20] , 其对创新的直接作用主要体现在对 创新产出的保护、 创新投入的引导和创新活动的激 励上。首先, 绿色服务产业政策通过提供知识产权 保护等政策工具, 优化企业成果转化、 产业化、 技术 转移的外部环境, 对企业技术创新活动予以正向激 励, 提高绿色技术创新的市场效益 [21] [22] 。 3 模型、 变量与数据…”
unclassified